2017 UKSim-AMSS 19th International Conference on Computer Modelling &Amp; Simulation (UKSim) 2017
DOI: 10.1109/uksim.2017.30
|View full text |Cite
|
Sign up to set email alerts
|

Power Curve Modelling for Wind Turbines

Abstract: The wind turbine power curve WTPC describes the relationship between wind speed and turbine power output. Power curve, provided by the manufacturer is one of the most important tools used to estimate turbine power output and capacity factor. Hence, an accurate WTPC model is essential for predicting wind energy potential. This paper presents a comparative study of various models for mathematical modelling of WTPC based on manufacturer power curve data gathered from 32 wind turbines ranging from 330 to 7580 kW. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…One of the most important parameters in determining electric power obtained from wind-based resources is wind speed. The general equation relating wind power to swept area ( ), wind speed ( ), density of air ( ) , wind turbine power coefficient ( ) and rated power is [39]:…”
Section: Wind Speed Effect Functionmentioning
confidence: 99%
“…One of the most important parameters in determining electric power obtained from wind-based resources is wind speed. The general equation relating wind power to swept area ( ), wind speed ( ), density of air ( ) , wind turbine power coefficient ( ) and rated power is [39]:…”
Section: Wind Speed Effect Functionmentioning
confidence: 99%
“…The calculation of wind turbine power output should be accomplished based on the wind turbine power curve provided by the manufacturer. In this study, the wind turbine power output calculation is conducted using the following relation [42]:…”
Section: Univariate Wind Prediction Modelmentioning
confidence: 99%
“…where P r is the maximum power output of a wind turbine rated at wind velocity v r , v min, and v max are the cut-in and cut-off wind velocities, respectively. Finally, P f (v) is the non-linear part of the power curve, representing the power output at wind velocity v. In this study, we utilize the power coefficient-based model given by reference [42]:…”
Section: Univariate Wind Prediction Modelmentioning
confidence: 99%
“…Besides the theoretical model, there are some other models, which are predicted by sampling the turbine output power at various wind speed. In [35], nine power curves models have been presented and compared, including linear model, general model, quadratic model, cubic-I model, cubic-II model, exponential model, power-coefficient model, approximate power-coefficient model, and polynomial model. Through the comparison results, it is observed that the power-coefficient model has the most accurate results.…”
Section: Power Curve Modeling Of the Offshore Turbinesmentioning
confidence: 99%
“…where C p,eq is the equivalent power coefficient, which is a constant for the variable-speed wind turbines operating in the range between the cut-in and rated wind speed [35,36]. In this study, it is assumed to be 0.42 [36].…”
Section: Power Curve Modeling Of the Offshore Turbinesmentioning
confidence: 99%